Художня трансформація образу козацтва в поезії "української школи" польського романтизму - Цьолик, Наталія; Tsolyk, Natalay (Східноєвропейський національний університет імені Лесі Українки, 2013)
В статті проаналізовано еволюцію образу козацтва в поезії «української школи» польського романтизму. Образ козака, поширений у польській літературі першої половини XIX ст., став для представників школи своєрідним ідейним центром. З’ясовано, що образ козацтва характеризується відносністю зображення. Усталені стереотипи образу козака в поезії «української школи», висвітлено в контексті та на підставі опозиції «свій–чужий».The paper analyzes the evolution of the Cossacks images in the «Ukrainian school» poetry of Polish Romanticism. Outlook study – present and future of Cossack image in Polish poetry of the romantic period is given. The image of the Cossacks was common and popular in the Polish literature in the first half of the XIX century. It became a kind of ideological center for all members of the school. The implementation of a variety of Cossack images in Polish romantic poetry by the «Ukrainian school» in typological comparison is examined. It was found that the Cossacks image is characterized by some relativity such as Cossack-Warrior, Knight, rebel, characternik, and music etc. The ideas of Cossacks and their role in the state formation by the representatives of this school are studied. Hardened stereotypes of Cossacks image in the «Ukrainian school» poetry are highlighted in context and on the basis of the opposition «friend» or «foe».
Literal transformation of Cossacks images in the «Ukrainian school» of Polish Romanticism style
Keywords: романтизм; «українська школа»; образ козака; опозиція «свій–чужий»; стереотип; Romanticism; «Ukrainian school»; Cossack image; opposition «friend» or «foe»; stereotype